2019
DOI: 10.1002/ece3.5371
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and community structure of small pest rodents (Muridae) in cultivated and fallow fields in maize‐growing areas in Mayuge district, Eastern Uganda

Abstract: Pest rodents remain key biotic constraints to cereal crops production in the East African region where they occur, especially in seasons of outbreaks. Despite that, Uganda has scant information on rodents as crop pests to guide effective management strategies. A capture–mark–recapture (CMR) technique was employed to study the ecology of small rodents, specifically to establish the species composition and community structure in a maize‐based agro ecosystem. Trapping of small rodents was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…As expected, diversity of the small mammals was lowest in the cropland compared to the non-crop habitats (including homestead). The results are in agreement with Demeke et al (2007), Mayamba et al (2019) and Shilereyo et al (2019) who also reported higher small mammal diversities in non-cultivated areas than in agricultural fields in Ethiopia (Arba Minch area), Uganda and Tanzania, respectively. The low small mammal species diversity in cropland can be ascribed to higher disturbance due to human activities including; land preparation (ploughing), weeding, thinning of young plants (particularly maize) and harvesting.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, diversity of the small mammals was lowest in the cropland compared to the non-crop habitats (including homestead). The results are in agreement with Demeke et al (2007), Mayamba et al (2019) and Shilereyo et al (2019) who also reported higher small mammal diversities in non-cultivated areas than in agricultural fields in Ethiopia (Arba Minch area), Uganda and Tanzania, respectively. The low small mammal species diversity in cropland can be ascribed to higher disturbance due to human activities including; land preparation (ploughing), weeding, thinning of young plants (particularly maize) and harvesting.…”
Section: Discussionsupporting
confidence: 92%
“…The habitat heterogeneity hypothesis explains that heterogeneous habitats support high species diversity due to increased microhabitats that provide more niches for coexisting species (August, 1983 ; Stein & Kreft, 2015 ). Heterogeneous habitats or habitat patches affect rodent diversity, abundance, and community assemblages through the provision of alternative microhabitats that serve as refuges and provide limiting resources to habitat generalists (Cramer & Willig, 2002 ; Mayamba et al, 2019 , 2020 ; Stein & Kreft, 2015 ). The influence of vegetation structure has been a central focus in the community ecology of small mammals including rodents (Cramer & Willig, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous habitats or habitat patches affect rodent diversity, abundance, and community assemblages through the provision of alternative microhabitats that serve as refuges and provide limiting resources to habitat generalists (Cramer & Willig, 2002;Mayamba et al, 2019Mayamba et al, , 2020Stein & Kreft, 2015). The influence of vegetation structure has been a central focus in the community ecology of small mammals including rodents (Cramer & Willig, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Rodents are one the most numerous invasive species globally (Buckle & Smith, 1994), damaging maize crops ( Zea mays ) and other crops at different stages of growth, leading to great economic loss, threatening food security and the potential spread of diseases (Mayamba, et al, 2019). Rodents have mainly been controlled through the use of anticoagulants (which are hazardous to the environment and cause secondary poisoning on rodent-eating carnivores) (Mdangi, et al, 2016), traps (whose effectiveness is low as most of them catch a single rodent at any moment) and cats (which are low in numbers, hence their effectiveness on a large scale is low) (Mahlaba, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%